Elevated expression of TIGIT on CD3+CD4+ T cells correlates with disease activity in systemic lupus erythematosus - Luo, Qing; Ye, Jianqing; Zeng, Lulu; Li, Xue; Fang, Le; Ju, Beihua; Huang, Zikun; Li, Junming (Allergy, asthma, and clinical immunology, 2017)
It is well-known that lymphocytes play an important role in systemic lupus erythematosus (SLE). T cell immunoreceptor with Ig and immunoreceptor tyrosine-based inhibitory domains (TIGIT) is one of immunosuppressive costimulatory molecules that mediates an inhibitory effect. However, its roles in SLE are poorly understood. This study was designed to investigate the correlation between the frequencies of TIGIT-expressing CD3 CD4 T lymphocytes and SLE. Patients with SLE were recruited from the First Affiliated Hospital of Nanchang University. Medical history, clinical manifestations, physical examination and laboratory measurements were recorded. The expression of TIGIT on CD3 T lymphocytes, B lymphocytes, monocytes, neutrophils, CD3 CD4 T lymphocytes and CD3 CD8 T lymphocytes were determined by flow cytometry. The frequencies of TIGIT-expressing CD3 CD4 T lymphocytes in patients with SLE were further analyzed for correlations with markers of autoimmune response, inflammation, urine proteins and disease activity in SLE. The frequency of TIGIT-expressing CD3 CD4 T lymphocytes was significantly elevated in SLE patients compared with healthy controls (P < 0.0001). The frequency of TIGIT-expressing CD3 CD4 T lymphocytes in patients with SLE was increased significantly in subjects with high anti-dsDNA titer (P = 0.026), high anti-Sm titer (P = 0.026), and high levels of urine microalbumin (P = 0.046). Furthermore, The frequency of TIGIT-expressing CD3 CD4 T lymphocytes was found to be positively correlated with the Disease Activity Index (SLEDAI) score in SLE (r = 0.082; P = 0.044). In SLE, the frequency of TIGIT-expressing CD3 CD4 T lymphocytes was elevated and associated with the disease activity.